Phenol Derivatives as Co-Crystallized Templates to Modulate Trimesic-Acid-Based Hydrogen-Bonded Organic Molecular Frameworks - Guangchuan Ou; Qiong Wang; Qiang Zhou; Xiaofeng Wang (Crystals, 2021)
Five host−guest trimesic-acid-based hydrogen-bonds framework compounds with different guests, namely [(TMA)4·(TMB)3] (1), [(TMA)2·(DMB)1.5] (2), [(TMA)6·(MP)] (3), [(TMA)·(EP)] (4) and [(TMA)·(PP)] (5) (TMA = trimesic acid, TMB = 1,3,5-trimethoxybenzene, DMB = 1,4-dimethoxybenzene, MP = 4-methoxyphenol, EP = 4-ethoxyphenol and PP = 4-propoxyphenol), were obtained through co-crystallization, and were characterized by elemental analysis, infrared spectroscopy analysis, and thermogravimetric analysis. The trimesic acid molecules comprise a hydrogen bonding six-membered cyclic host network that is found in a two-dimensional arrangement in compounds 1 and 2, and in a nine-fold interpenetrated three-dimensional structure in compound 3. In compounds 4 and 5, the trimesic acid and EP/PP molecules form a hydrogen-bonded six-membered cyclic network, resulting in a one-dimensional chain structure through O−H…O hydrogen bonds.